Focal adhesion kinases crucially regulate TGFβ-induced migration and invasion of bladder cancer cells via Src kinase and E-cadherin - Kong, De-Bo (Onco Targets Ther, 2017)
Focal adhesion kinase (FAK) is a non-receptor protein-tyrosine kinase that is triggered off by special extracellular signals such as some growth factors and integrins. FAK is found in cell–matrix attachment sites and implicated in cell migration, invasion, movement, gene expression, survival and apoptosis. In this study, we aimed to investigate whether FAK plays a role in invasion and migration of bladder cancer cells. Using an FAK-specific small interfering RNA (siRNA) and an FAK inhibitor PF-228, we found that inhibition of FAK tyrosine phosphorylation or knockdown of FAK suppressed invasion and migration of bladder cancer cells. Src is an important mediator of FAK-regulated migratory and invasive activity. Tyrosine phosphorylation of Src and FAK is mutually dependent and plays a key role in transforming growth factor beta (TGFβ)-induced invasion and migration. E-cadherin acts downstream of FAK and is a critical negative regulator in FAK-regulated invasion and migration of bladder cancer cells. These findings imply that FAK is involved in oncogenic signaling of invasion and migration, which can be a novel therapeutic target to treat patients with bladder cancer.